Original paperEGSnrc Monte Carlo-aided dosimetric studies of the new BEBIG 60Co HDR brachytherapy source - Anwarul, Islam Mohammad; Akramuzzaman, Mir Md.; Zakaria, Golam Abu (Journal of Contemporary Brachytherapy, 2013)
Purpose : The purpose of this study is to obtain the dosimetric parameters of the new BEBIG 60 Co brachytherapy source following by TG-43U1 recommendation with appropriate electron cutoff energy (0.521 MeV). Material and methods : The new BEBIG 60 Co brachytherapy source is used to calculate the TG-43U1 parameters. EGSnrc-based Monte Carlo simulation code has been used to calculate the radial dose functions and anisotropy functions. 2D dose rate table is obtained with Cartesian coordinate system for surrounding the source. Results: The radial dose functions are calculated for the distance of 0.06 cm to 100 cm from the source center with different cutoff energies and compared. The anisotropy functions values are calculated with the range of 1° to 179°, and apart from 0.2 cm to 20 cm of radial distances. The along-away dose rate data are calculated for quality assurance purposes. The calculated values are compared with the consensus data set and previous published results. Conclusions : The radial dose function values from 0.06 cm to 0.16 cm are low, and these values gradually increased up to 0.3 cm radial distance. The radial dose function values are compared with the values of consensus data set using EGSnrc code system, and it is in good agreement with the published data range. The data for < 0.1 cm is not available in consensus data set, and extrapolated value is included for 0 distances which is the same as the value of 0.1 cm. In this study, the obtained values are strictly fall-off to < 0.1 cm distances. Good agreement with the published data was observed, except the values less than 40° angle at 0.5 cm distance for anisotropy function values.